Armor stories - Bengan, John (Bughaw, 2022)
Terror, longing, and defiance recur in these thirteen stories about people trying “to live happily every so often” despite the prevalence of summary executions, the megalomania of a once and future strongman, and the indifference of witnesses. In one story, a Death Squad recruit goes on his first day on the job. In another, a drug user joins a Miss Gay beauty pageant perhaps for the last time. Meanwhile, a vigilante mayor disguised as a taxi driver prowls the city at night.